Solid electrolyte and battery

By using elements such as Li, Zr, Ta, Gd, Yb and Cl in solid electrolytes, combined with specific molar ratios and treatment methods, the problem of insufficient stability of existing solid electrolytes is solved, and high lithium ion conductivity and stability are achieved The dual effect of sex.

CN119487582APending Publication Date: 2025-02-18NGK INSULATORS LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046392.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-28
Filing Date
2023-07-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing solid electrolytes have insufficient stability, resulting in a decrease in lithium ion conductivity and cannot meet the needs of miniaturization and increased reliability.

Method used

A solid electrolyte containing Li, Zr, Ta, Gd, or Yb and Cl is used to form a material with high lithium ion conductivity and stability through a specific molar ratio and treatment method.

Benefits of technology

While achieving high lithium ion conductivity, the stability of the electrolyte is improved, the reduction of lithium ion conductivity is avoided, and the needs of miniaturization and reliability are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487582A_ABST
    Figure CN119487582A_ABST
Patent Text Reader

Abstract

The solid electrolyte contains A, M [alpha], M [beta], M [gamma], and Cl, where A is at least one element selected from the group consisting of Li and Na, M [alpha] is at least one element selected from the group consisting of Zr and Hf, M [beta] is at least one element selected from the group consisting of Ta and Nb, M [gamma] is at least one element selected from the group consisting of Gd, Yb, Dy, Er, Ho, Eu, and Sc, and the amount of substance of Cl is greater than the amount of substance of A. As a result, it is possible to provide a solid electrolyte having high ionic conductivity and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte and a battery.

[0002] [References to related applications]

[0003] This application claims the priority benefit of International Patent Application No. PCT / JP2022 / 26960 filed on July 7, 2022 and International Patent Application No. PCT / JP2023 / 12626 filed on March 28, 2023, and all disclosed contents of these applications are incorporated into this application. Background Art

[0004] In recent years, there has been a strong demand for miniaturization and improved reliability (safety) of batteries that serve as power sources for electronic devices. Therefore, attention has been paid to all-solid batteries using solid electrolytes. In addition, as sulfur-free solid electrolytes, halides, Li 3 YC 6 It exhibits high lithium ion conductivity at room temperature (for example, see Japanese Patent No. 6934626 (Document 1)). International Publication No. 2020 / 070956 (Document 2) discloses a Li 6-4b+ab (Zr 1-a M a ) b X 6 Here, M is at least one element selected from the group consisting of Al, Ga, Bi, Sc, Sm and Sb, X is a halogen element, and 0<a<1 and 0<b<1.5 are satisfied.

[0005] In addition, "Na 2 ZrCl 6 Enabling highly stable 3Vall-solid-state Na-ion batteries”(Energy Storage Materials, 2021, Vol. 37, pp. 47-54)(Reference 3) reported: Na 2 ZrCl 6 It shows high sodium ion conductivity at room temperature. In addition, the specification of U.S. Patent Application Publication No. 2021 / 43966 (Document 4) discloses a method comprising (Li x M1 y )(M2) 3-δ (M3) 2-ω O 12-z X z The oxide of the compound represented by has a garnet structure. In addition, Example 19 of Document 4 discloses a Li6.8 La 3 Zr 0.4 Hf 0. 4 Sn 0.4 Sc 0.4 Nb 0.4 O 11.8 Cl 0.2 Represents oxide.

[0006] However, the inventors of the present application prepared the chloride electrolyte powder disclosed in Documents 1 and 2 and placed it in a dry room with a dew point controlled at -40°C. As a result, the electrolyte decomposed and could not maintain the initial lithium ion conductivity, that is, it was found that the stability was low. 2 ZrCl 6 , and it was also found that the stability was low. Summary of the invention

[0007] The present invention relates to a solid electrolyte, and an object of the present invention is to provide a solid electrolyte having high ion conductivity and high stability.

[0008] The invention of Scheme 1 is a solid electrolyte comprising A, Mα, Mβ, Mγ and Cl, wherein A is at least one element selected from the group consisting of Li and Na, Mα is at least one element selected from the group consisting of Zr and Hf, Mβ is at least one element selected from the group consisting of Ta and Nb, Mγ is at least one element selected from the group consisting of Gd, Yb, Dy, Er, Ho, Eu and Sc, and the amount of Cl is greater than the amount of A.

[0009] According to the present invention, a solid electrolyte having high ion conductivity and high stability can be provided.

[0010] The invention of Scheme 2 is based on the solid electrolyte of Scheme 1, wherein A contains Li.

[0011] The invention according to claim 3 is the solid electrolyte according to claim 1 or 2, wherein Mα contains Zr.

[0012] The invention according to claim 4 is the solid electrolyte according to any one of claims 1 to 3, wherein Mβ contains Ta.

[0013] The invention according to claim 5 is the solid electrolyte according to any one of claims 1 to 4, wherein Mγ contains Gd or Yb.

[0014] The invention of claim 6 is based on any one of the solid electrolytes of claims 1 to 5 and is represented by the following composition formula:

[0015] A 6-(4+a-b)(1+c) (Mα (1-a-b) Mβ a Mγb ) 1+c Cl 6

[0016] It satisfies 0<a, 0<b, a+b<1 and -0.2≤c≤0.2.

[0017] The invention of claim 7 is based on any one of the solid electrolytes of claims 1 to 6, wherein A is Li, and a value obtained by dividing the average ionic radius of Li, Mα, Mβ and Mγ by the ionic radius of Cl is less than 0.424.

[0018] The invention of claim 8 is based on any one of the solid electrolytes of claims 1, 3 to 6, wherein A is Na, and a value obtained by dividing the average ionic radius of Na, Mα, Mβ and Mγ by the ionic radius of Cl is less than 0.526.

[0019] The invention of claim 9 is based on any one of the solid electrolytes of claims 1 to 8, but does not contain a garnet structure.

[0020] The invention according to claim 10 is a battery comprising the solid electrolyte according to any one of claims 1 to 9.

[0021] The above-mentioned object and other objects, features, aspects and advantages will become more apparent from the following detailed description of the present invention with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a longitudinal cross-sectional view showing an all-solid lithium ion secondary battery. DETAILED DESCRIPTION

[0023] Figure 1 1 is a longitudinal cross-sectional view showing an all-solid lithium ion secondary battery 1 (hereinafter referred to as "all-solid secondary battery 1"). Figure 1 The positive electrode 11, the electrolyte layer 13 and the negative electrode 12 are sequentially provided above the positive electrode 11 and the negative electrode 12. That is, the electrolyte layer 13 is provided between the positive electrode 11 and the negative electrode 12. The electrolyte layer 13 is a solid electrolyte layer and also serves as a separator layer. The positive electrode 11 includes a current collector 111 and a positive electrode layer 112. The positive electrode layer 112 contains a positive electrode active material. The negative electrode 12 includes a current collector 121 and a negative electrode layer 122. The negative electrode layer 122 contains a negative electrode active material.

[0024] The positive electrode active material of the positive electrode layer 112 preferably includes a lithium composite oxide. A preferred positive electrode active material is a lithium composite oxide having a layered rock salt structure, such as NCM (Li(Ni, Co, Mn)O 2 The positive electrode active material may also be other lithium composite oxides, for example, NCA (Li(Ni, Co, Al)O 2 )、LCO(LiCoO2 ), LNMO (LiNi 0.5 Mn 1.5 O 4 ), LFP (LiFePO 4 ) etc. The positive electrode layer 112 contains, in addition to the positive electrode active material, a solid electrolyte and an electron conduction aid (carbon black, etc.) described later. The positive electrode layer 112 in this embodiment is obtained by integrating these materials by pressurization and heating.

[0025] Examples of the negative electrode active material of the negative electrode layer 122 include LTO (Li 4 Ti 5 O 12 )、NTO(Nb 2 TiO 7 ), TiO 2 (titanium oxide), graphite, SiO (silicon monoxide) and other compounds. In addition to the negative electrode active material, the negative electrode layer 122 also contains a solid electrolyte described later. The negative electrode layer 122 may further contain an electron conduction aid (carbon black, etc.). The negative electrode layer 122 in this embodiment is obtained by integrating these substances by pressurizing and heating.

[0026] The configuration and material of the positive electrode 11 and the negative electrode 12 of the all-solid secondary battery 1 are not limited to the configuration and material described above, and other various configurations and materials may be adopted.

[0027] The electrolyte layer 13 is composed of a solid electrolyte (hereinafter also referred to as "the present solid electrolyte") according to an embodiment of the present invention, or includes the solid electrolyte. The solid electrolyte is a lithium (Li) ion conductive material. The solid electrolyte includes: lithium (Li) element, three other metal elements (Mα, Mβ, Mγ) in the form of cations, and chlorine (Cl) element. The solid electrolyte may be composed of Li, Mα, Mβ, Mγ, and Cl.

[0028] Mα is an element in the form of a tetravalent cation, and is at least one element selected from the group consisting of zirconium (Zr) and hafnium (Hf). Mβ is an element in the form of a pentavalent cation, and is at least one element selected from the group consisting of tantalum (Ta) and niobium (Nb). Mγ is an element in the form of a trivalent cation, and is at least one element selected from the group consisting of gadolinium (Gd), ytterbium (Yb), dysprosium (Dy), erbium (Er), holmium (Ho), europium (Eu) and scandium (Sc). In the solid electrolyte that contains at least one trivalent, tetravalent, and pentavalent element in addition to Li as a cation, high lithium ion conductivity and high stability can be achieved as described later. In addition, hydrogen sulfide gas is not generated in the solid electrolyte, and therefore, a highly safe all-solid secondary battery 1 can be provided.

[0029] In the present solid electrolyte, Mα preferably contains Zr, and Mα may also be only Zr. Thus, as described later, the decrease in lithium ion conductivity caused by the influence of water in the air, etc. can be suppressed, thereby more reliably improving stability. Mβ preferably contains Ta, and Mβ may also be only Ta. Thus, as in the embodiments described later, the lithium ion conductivity can be restored by heat treatment. Mγ preferably contains Gd or Yb, and Mγ may also be only Gd or Yb, or may also be only Gd and Yb. Thus, as in the embodiments described later, the lithium ion conductivity just after synthesis (initial) can be more reliably improved. The amount of Li is greater than the amount of any one of Mα, Mβ and Mγ, for example, and is preferably greater than the sum of the amounts of Mα, Mβ and Mγ. In one example, the amount of Mα is greater than the amount of any one of Mβ and Mγ, but it may also be less than the amount of any one of Mβ and Mγ. Typically, the amount of Cl is greater than the amount of Li. The amount of Cl may be greater than, for example, the amount of any one of Li, Mα, Mβ, and Mγ, or may be greater than the total amount of Li, Mα, Mβ, and Mγ.

[0030] A preferred solid electrolyte is a compound represented by the following composition formula (1):

[0031] Li 6-(4+a-b)(1+c) (Mα (1-a-b) Mβ a Mγ b ) 1+c Cl 6 ···(1)

[0032] 0<a, 0<b, a+b<1 and -0.2≤c≤0.2 are satisfied. Regarding a and b, 0.1≤a≤0.4 and 0.1≤b≤0.4 may be satisfied. In addition, 0.1≤a+b≤0.6 may be satisfied. Regarding c, -0.1≤c≤0.1 may be satisfied, and c may be 0. The solid electrolyte may be crystalline or amorphous.

[0033] When confirming whether an unknown solid electrolyte is the present solid electrolyte, a chemical analysis is performed on the unknown solid electrolyte to confirm whether the constituent elements are Li, Mα, Mβ, Mγ, and Cl. In confirming whether the unknown solid electrolyte is the above composition formula (1), Li, Mα, Mβ, and Mγ can be quantified using, for example, ICP-emission spectrometry. Cl can be quantified using, for example, ion chromatography.

[0034] The molar ratio of Li, Mα, Mβ, Mγ and Cl in the above composition formula (1) is Li: Mα: Mβ: Mγ: Cl = 6-(4+a-b)(1+c): (1-a-b)(1+c): a(1+c): b(1+c): 6. It is considered that if the value of Li in the molar ratio obtained by analyzing the unknown solid electrolyte is 0.90×{6-(4+a-b)(1+c)} or more and 1.10×{6-(4+a-b)(1+c)} or less, then Li satisfies the above composition formula (1). The value of Li is more preferably 0.95×{6-(4+a-b)(1+c)} or more and 1.05×{6-(4+a-b)(1+c)} or less. The same is true for Mα, Mβ and Mγ.

[0035] In a preferred solid electrolyte, the value obtained by dividing the average ionic radius of Li, Mα, Mβ and Mγ by the ionic radius of Cl (hereinafter referred to as the "average ionic radius ratio") is less than 0.424. The average ionic radius ratio is more preferably less than 0.422, and further preferably less than 0.420. In such a solid electrolyte, as described later, stability can be more reliably improved. The lower limit of the average ionic radius ratio is not particularly limited, for example, 0.395. The average ionic radius (rc) of Li, Mα, Mβ and Mγ contained in the solid electrolyte is calculated based on mathematical formula 1.

[0036] (Mathematical formula 1)

[0037] rc=Σ(rC·RC) / ΣRC

[0038] Here, rC represents the ionic radius of the elements (i.e., cations) contained in Li, Mα, Mβ, and Mγ. RC represents the amount of substance of each element. The average ionic radius ratio (rc / ra) is obtained by dividing the average ionic radius (rc) of Li, Mα, Mβ, and Mγ by the ionic radius (ra) of Cl. It is believed that in a solid electrolyte with an average ionic radius ratio of less than 0.424, the bonding distance between the cation and Cl becomes shorter, and the bonding force between the cation and Cl increases. In addition, it is estimated that the height of the bonding force improves the stability of the material.

[0039] For example, the present solid electrolyte is manufactured by the following method. First, a powder containing a chloride of Li, a powder containing a chloride of Mα, a powder containing a chloride of Mβ, and a powder containing a chloride of Mγ are prepared. The chloride containing Li is, for example, LiCl. The chloride containing Mα is, for example, MαCl 4 The chloride containing Mβ is, for example, MβCl 5 The chloride containing Mγ is, for example, MγCl 3 . These powders are weighed and mixed according to the specified molar ratio.

[0040] Next, the mixture is subjected to a milling treatment (mechanical chemical milling). Here, in one example of the milling treatment, a planetary ball mill is used. In the planetary ball mill, the container rotates and the table carrying the container revolves, so that it can generate very high impact energy. The milling treatment can also be performed using other types of pulverizers. Through the above-mentioned milling treatment, a powder of the present solid electrolyte for the positive electrode layer 112, the negative electrode layer 122 or the electrolyte layer 13 is obtained. In this treatment example, the milling treatment is performed at room temperature, but conditions such as temperature can be appropriately changed. The present solid electrolyte can also be manufactured by treatments other than milling treatments such as sintering.

[0041] The present solid electrolyte may contain sodium (Na) instead of Li, or may contain Na together with Li. That is, the solid electrolyte contains A, Mα, Mβ, Mγ and Cl, and A is at least one element selected from the group consisting of Li and Na. Mα, Mβ and Mγ are the same as above. When A is Na, high (sodium) ion conductivity and high stability can also be achieved as described later. The solid electrolyte may be composed of A, Mα, Mβ, Mγ and Cl. In this case, the total mass of A, Mα, Mβ, Mγ and Cl relative to the overall mass of the solid electrolyte is, for example, 95% by mass or more. Typically, the amount of Cl is greater than the amount of A. The amount of Cl may be greater than the amount of any element contained in the solid electrolyte. The present solid electrolyte is different from the oxide described in the specification of U.S. Patent Application Publication No. 2021 / 43966 (the above-mentioned document 4), and preferably does not contain a garnet structure. Whether a garnet structure is contained can be confirmed by X-ray diffraction analysis.

[0042] When the solid electrolyte contains Na, the above composition formula (1) is expressed as the following composition formula (2):

[0043] A 6-(4+a-b)(1+c) (Mα (1-a-b) Mβ a Mγ b ) 1+c Cl 6 ···(2)

[0044] Similar to the composition formula (1), 0<a, 0<b, a+b<1, and -0.2≤c≤0.2 are satisfied. In addition, Na can be quantified by ICP-emission spectrometry or the like.

[0045] In a preferred solid electrolyte where A is Na, the value obtained by dividing the average ionic radius of Na, Mα, Mβ and Mγ by the ionic radius of Cl (hereinafter, referred to as the "average ionic radius ratio" as in the case where A is Li) is less than 0.526. The average ionic radius ratio is more preferably less than 0.520, and further preferably less than 0.515. In such a solid electrolyte, as described later, stability can be more reliably improved. The lower limit of the average ionic radius ratio is not particularly limited, for example, 0.480. The average ionic radius ratio when A is Na is solved in the same way as when A is Li.

[0046] In the manufacture of a solid electrolyte in which A is Na, a powder containing Na chloride is used instead of a powder containing Li chloride. The chloride containing Na is, for example, NaCl. In addition, a powder containing Na chloride, a powder containing Mα chloride, a powder containing Mβ chloride, and a powder containing Mγ chloride are mixed and milled to obtain a powder of a solid electrolyte in which A is Na.

[0047] The all-solid secondary battery 1 using the solid electrolyte in which A contains Na may be an all-solid sodium ion secondary battery. In this case, the positive electrode active material of the positive electrode layer 112 may be, for example, a layered compound of NaCoO 2 、NaNiO 2 、NaMnO 2 、Na(Ni,Co,Mn)O 2 、NaFeO 2 、Na(Fe,Mn)O 2 、Na(Ni、Mn、Fe、Ti)O 2 etc., spinel type NaMn 2 O 4 etc., polyanionic Na 3 V 2 (PO 4 ) 3 、Na 2 Fe 2 (SO 4 ) 3 、NaFePO 4 、Na 4 Fe 7 (PO 4 ) 6 、Na 3 V(PO 3 ) 3 N, etc. In addition, examples of the negative electrode active material of the negative electrode layer 122 include metals such as Na, In, Sn, and Sb, Na alloys, graphite, hard carbon, Na 4 / 3 Ti 5 / 3 O4 、Na 2 Ti 6 O 13 、Na 0.66 [Li 0.22 Ti 0.78 ]O 2 、Na 3 V 2 (PO 4 ) 3 , SnO, etc. A contains Li and Na, and the ions conducted in the all-solid secondary battery 1 may be both Li ions and Na ions.

[0048] Next, examples and comparative examples of the present solid electrolyte when A is Li are described. Tables 1 and 2 show the compositions, evaluation results, etc. of the solid electrolytes of Examples 1 to 21.

[0049] [Table 1]

[0050]

[0051] [Table 2]

[0052]

[0053] (Example 1)

[0054] [Preparation of electrolyte]

[0055] In an argon atmosphere with a dew point of -60°C or less, LiCl and ZrCl 4 、TaCl 5 and GdCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 =1.7:0.5:0.4:0.1 molar ratio, these raw material powders were weighed, crushed and mixed in a mortar, the obtained mixed powder was put into a zirconia container together with zirconia balls, and milled at 300 rpm for 20 hours using a planetary ball mill to obtain a solid electrolyte powder.

[0056] [Exposure test]

[0057] The solid electrolyte powder was placed in a shallow dish and allowed to stand (exposed) in a drying room controlled at a dew point of -40°C for 16 hours.

[0058] [Heat treatment]

[0059] The solid electrolyte powder was left standing (exposed) in a drying chamber for 16 hours and then heat-treated at 150°C.

[0060] [Conductivity measurement]

[0061] The solid electrolyte powder was placed in a mold consisting of a resin sleeve and upper and lower punches made of SUS (stainless steel), and uniaxial pressing was performed at a pressure of 150 MPa. Lead wires were connected to the upper and lower punches, and impedance measurement was performed at room temperature to calculate the lithium ion conductivity (sodium ion conductivity in Examples 22 to 23 and Comparative Examples 10 to 11 described later, hereinafter referred to as "ion conductivity").

[0062] [Stability evaluation]

[0063] The impedance of the solid electrolyte powder just after milling (after synthesis) using a planetary ball mill, the solid electrolyte powder exposed in a drying room for 16 hours, and the solid electrolyte powder subjected to heat treatment after exposure was measured, and the ion conductivity was calculated. In Table 1, the ion conductivity of the solid electrolyte powder just after milling (i.e., initial conductivity) is shown in the "After Synthesis" column, the ion conductivity of the solid electrolyte powder exposed in a drying room for 16 hours is shown in the "Exposure 16h" column, and the ion conductivity of the solid electrolyte powder subjected to heat treatment after exposure is shown in the "Exposure 16h + Heat Treatment" column (the same applies to Table 2, Table 3 and Table 4 described later).

[0064] In addition, in the stability evaluation, the maintenance rate of ion conductivity was calculated. The maintenance rate of ion conductivity after exposure for 16 hours was obtained by (100×(ion conductivity after exposure for 16 hours) / (ion conductivity after synthesis)). The maintenance rate of ion conductivity after exposure for 16 hours + heat treatment was obtained by (100×(ion conductivity after exposure for 16 hours + heat treatment) / (ion conductivity after synthesis)).

[0065] [Calculation of average ionic radius ratio]

[0066] The average ionic radius ratio of the solid electrolyte of Example 1 is calculated using the above-mentioned mathematical formula 1. Here, in the solid electrolyte of Example 1, Li, Zr, Ta and Gd are included as cations, and Cl is included as an anion. The ionic radii (coordination number 6) of Li, Zr, Ta, Gd and Cl are respectively and The molar ratio of Li, Zr, Ta and Gd is 1.700:0.500:0.400:0.100. Therefore, the average ionic radius rc of the cation is calculated by (1.700×0.76+0.500×0.72+0.400×0.64+0.100×0.938) / (1.700+0.500+0.400+0.100), and the result is The ionic radius ra of the anion is Therefore, the average ion radius ratio was calculated by rc / ra, and the result was 0.410. In the column "satisfying rc / ra<0.424" in Table 1, when the average ion radius ratio is less than 0.424, it is evaluated as "○", and when the average ion radius ratio is greater than 0.424, it is evaluated as "×" (the same in Tables 2 and 3).

[0067] (Example 2)

[0068] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and GdCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the above-mentioned compounds was 0.6:0.3:0.1.

[0069] (Example 3)

[0070] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and GdCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above compounds was 0.7:0.2:0.1.

[0071] (Example 4)

[0072] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and GdCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 2.0:0.8:0.1:0.1.

[0073] (Example 5)

[0074] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and GdCl3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 0.5:0.3:0.2.

[0075] (Example 6)

[0076] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and GdCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above compounds was 2.0:0.6:0.2:0.2.

[0077] (Example 7)

[0078] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and GdCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the two components was 0.5:0.7:0.1:0.2.

[0079] (Example 8)

[0080] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and GdCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 2.1:0.5:0.2:0.3.

[0081] (Example 9)

[0082] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5and GdCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the above-mentioned compounds was 0.5:0.1:0.4.

[0083] (Example 10)

[0084] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and YbCl 3 For LiCl:ZrCl 4 :TaCl 5 :YbCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the above-mentioned components was 0.5:0.4:0.1.

[0085] (Example 11)

[0086] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and YbCl 3 For LiCl:ZrCl 4 :TaCl 5 :YbCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 0.5:0.3:0.2.

[0087] (Example 12)

[0088] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and YbCl 3 For LiCl:ZrCl 4 :TaCl 5 :YbCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 2.1:0.5:0.2:0.3.

[0089] (Example 13)

[0090] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl5 and YbCl 3 For LiCl:ZrCl 4 :TaCl 5 :YbCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the above-mentioned compounds was 0.5:0.1:0.4.

[0091] (Example 14)

[0092] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 , GdCl 3 and YbCl 3 For LiCl:ZrCl 4 :TaCl 5 :GdCl 3 :YbCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 2.2:0.4:0.2:0.2:0.2.

[0093] (Example 15)

[0094] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、NbCl 5 and YbCl 3 For LiCl:ZrCl 4 :NbCl 5 :YbCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 0.5:0.3:0.2.

[0095] (Example 16)

[0096] In the preparation of the electrolyte of Example 1, LiCl and HfCl 4 、TaCl 5 and YbCl 3 for LiCl:HfCl 4 :TaCl 5 :YbCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 0.5:0.3:0.2.

[0097] (Example 17)

[0098] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and HoCl 3 For LiCl:ZrCl 4 :TaCl 5 :HoCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above compounds was 0.7:0.2:0.1.

[0099] (Example 18)

[0100] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and DyCl 3 For LiCl:ZrCl 4 :TaCl 5 :DyCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above compounds was 0.7:0.2:0.1.

[0101] (Example 19)

[0102] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and ErCl 3 For LiCl:ZrCl 4 :TaCl 5 :ErCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above compounds was 0.7:0.2:0.1.

[0103] (Example 20)

[0104] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and ScCl 3 For LiCl:ZrCl 4 :TaCl 5 :ScCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the above-mentioned compounds was 0.6:0.3:0.1.

[0105] (Example 21)

[0106] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 、TaCl 5 and EuCl 3 For LiCl:ZrCl 4 :TaCl 5 :EuCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the above-mentioned compounds was 0.6:0.3:0.1.

[0107] Table 3 shows the compositions, evaluation results, and the like of the solid electrolytes of Comparative Examples 1 to 9.

[0108] [Table 3]

[0109]

[0110] (Comparative Example 1)

[0111] In the preparation of the electrolyte of Example 1, LiCl and YCl 3 For LiCl:YCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of MgCl2O3 and MgCl2O3 was ....

[0112] (Comparative Example 2)

[0113] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 For LiCl:ZrCl 4 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of MgCl2O3 and MgCl2O3 was ... and MgCl2O3 was MgCl2O3.

[0114] (Comparative Example 3)

[0115] In the preparation of the electrolyte of Example 1, LiCl and YbCl 3 For LiCl:YbCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of MgCl2O3 and MgCl2O3 was ....

[0116] (Comparative Example 4)

[0117] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 and SmCl 3 For LiCl:ZrCl 4 :SmCl 3An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the two compounds was 0.5:1:0.9:0.1.

[0118] (Comparative Example 5)

[0119] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 and BiCl 3 For LiCl:ZrCl 4 :BiCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the two compounds was 0.5:1:0.9:0.1.

[0120] (Comparative Example 6)

[0121] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 and GdCl 3 For LiCl:ZrCl 4 :GdCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the two compounds was 0.5:1:0.7:0.3.

[0122] (Comparative Example 7)

[0123] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 and YbCl 3 For LiCl:ZrCl 4 :YbCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the two compounds was 0.5:1:0.7:0.3.

[0124] (Comparative Example 8)

[0125] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 YCl 3 For LiCl:ZrCl 4 :YCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the two compounds was 0.5:0.5:0.5.

[0126] (Comparative Example 9)

[0127] In the preparation of the electrolyte of Example 1, LiCl and ZrCl 4 and TaCl5 For LiCl:ZrCl 4 :TaCl 5 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the two components was 0.5:1:0.7:0.3.

[0128] As shown in Tables 1 to 3, the ionic conductivity of the solid electrolytes of Examples 1 to 21 after synthesis is 4.8×10 -4 S / cm, and the ionic conductivity after exposure for 16 h was 3.9×10 -5 S / cm or more. On the other hand, in the solid electrolytes of Comparative Examples 1 to 9, at least one of the ionic conductivity after synthesis and the ionic conductivity after exposure for 16 hours is less than the above value. As such, the solid electrolytes of Examples 1 to 21 are materials having both high ionic conductivity and high stability. The solid electrolytes of Examples 1 to 21 also satisfy the above composition formula (1).

[0129] In addition, the solid electrolytes of Examples 1 to 8 and 10 to 21 have higher ionic conductivity after exposure for 16 h and ionic conductivity after exposure for 16 h + heat treatment than those of Comparative Examples 1 to 9. The ionic conductivity after exposure for 16 h + heat treatment is 1.0×10 - 4 S / cm or more. In addition, the maintenance rate of the ion conductivity after exposure for 16 hours is higher than that of Comparative Examples 1 to 9. Therefore, it is known that the solid electrolytes of Examples 1 to 8 and 10 to 21 having an average ion radius ratio (rc / ra) of less than 0.424 are materials with higher stability.

[0130] In the solid electrolytes of Examples 1 to 21, the detailed mechanism of improved stability is not yet clear, and it is believed that: as cations, in addition to Li, at least one trivalent, tetravalent, and pentavalent element is included, which contributes to stability. In addition, from the viewpoint of improved stability, it is preferred that the average ionic radius ratio is less than 0.424 as described above. The smaller average ionic radius ratio indicates that the bonding distance between the cation and Cl is shorter, and it is believed that the bonding force between the cation and Cl is higher. It is inferred that the height of the bonding force improves the stability as a material.

[0131] Comparing Comparative Examples 1 to 3, in Comparative Example 2 in which the solid electrolyte contains Zr, the ion conductivity after exposure for 16 hours is improved. In addition, in Examples 1 to 4 and Examples 5 to 7, there is a trend that if the ratio of Zr is increased, the ion conductivity after exposure for 16 hours is improved. Therefore, it is believed that the stability is more reliably improved by including Zr in the solid electrolyte. The reason is not clear, but it is believed that in the solid electrolyte containing Zr, the stability against water is confirmed to be improved, which contributes to the improvement of the ion conductivity after exposure for 16 hours. In addition, it is believed that when Hf, which is a tetravalent cation like Zr, is used instead of Zr, or when Hf is used together with Zr, the stability is also improved. In fact, in Example 16, Hf is used instead of Zr. In this case, when exposed for 16 hours, a higher ion conductivity to a certain extent is also obtained.

[0132] In Comparative Example 9, which contains Zr and Ta in addition to Li and Cl, the ionic conductivity after exposure for 16 hours + heat treatment is improved compared to Comparative Example 2 containing only Zr. In addition, in Examples 1 to 14, 16 to 21 containing Ta, the ionic conductivity after exposure for 16 hours + heat treatment is generally improved. Therefore, it is believed that by including Ta in the solid electrolyte, the ionic conductivity can be restored by heat treatment. It is believed that when Nb, which is a pentavalent cation like Ta and has the same ionic radius as Ta, is used instead of Ta, or when Nb is used together with Ta, the ionic conductivity is also easily restored by heat treatment. In fact, in Example 15, Nb is used instead of Ta. In this case, high ionic conductivity is also obtained when exposed for 16 hours + heat treatment.

[0133] In Comparative Examples 6 and 7 containing Zr and Gd or Yb in addition to Li and Cl, the ionic conductivity (initial conductivity) after synthesis is greatly improved compared to Comparative Example 2 containing only Zr. In addition, in Examples 1 to 16 containing Gd or Yb, the ionic conductivity after synthesis is generally improved. Therefore, it is believed that the ionic conductivity after synthesis is more reliably improved by including Gd or Yb in the solid electrolyte. It is believed that when Dy, Er, Ho, Eu and Sc, which are trivalent cations like Gd and Yb and have an ionic radius similar to that of Gd or Yb, are used instead of Gd or Yb, or when Dy, Er, Ho, Eu and Sc are used together with Gd or Yb, the ionic conductivity after synthesis is also improved. In fact, in Examples 17 to 21, Ho, Dy, Er, Sc and Eu are used respectively, and in this case, high ionic conductivity is also obtained after synthesis.

[0134] Next, the embodiments and comparative examples of the present solid electrolyte when A is Na are described. Table 4 shows the composition, evaluation results, etc. of the solid electrolytes of Examples 22 to 23 and Comparative Examples 10 to 11. In the column "Satisfying rc / ra<0.526" in Table 4, when the average ionic radius ratio is less than 0.526, it is evaluated as "○", and when the average ionic radius ratio is greater than 0.526, it is evaluated as "×". In addition, in the calculation of the average ionic radius ratio, the ionic radius of Na (coordination number 6) is

[0135] [Table 4]

[0136]

[0137] (Example 22)

[0138] In the preparation of the electrolyte of Example 1, NaCl and ZrCl 4 、TaCl 5 and GdCl 3 For NaCl:ZrCl 4 :TaCl 5 :GdCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the above-mentioned compounds was 0.6:0.3:0.1.

[0139] (Example 23)

[0140] In the preparation of the electrolyte of Example 1, NaCl and ZrCl 4 、TaCl 5 and YbCl 3 For NaCl:ZrCl 4 :TaCl 5 :YbCl 3 An electrolyte was prepared, tested and evaluated in the same manner as in Example 1 except that the molar ratio of the above-mentioned compounds was 0.5:0.3:0.2.

[0141] (Comparative Example 10)

[0142] In the preparation of the electrolyte of Example 1, NaCl and ZrCl 4 For NaCl:ZrCl 4 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of MgCl2O3 and MgCl2O3 was ... and MgCl2O3 was MgCl2O3.

[0143] (Comparative Example 11)

[0144] In the preparation of the electrolyte of Example 1, NaCl and ZrCl 4 and YbCl 3 For NaCl:ZrCl 4 :YbCl 3 An electrolyte was prepared in the same manner as in Example 1, and the test and evaluation were performed, except that the molar ratio of the two compounds was 0.5:0.5:0.5.

[0145] As shown in Table 4, the solid electrolytes of Examples 22 to 23 have higher ion conductivity after synthesis, ion conductivity after exposure for 16 hours, and ion conductivity after exposure for 16 hours + heat treatment than the solid electrolytes of Comparative Examples 10 to 11. In this way, in addition to Na, the Na ion conductor contains at least one trivalent, tetravalent, and pentavalent element as a cation, thereby also being able to obtain high initial conductivity and high stability. The solid electrolytes of Examples 22 to 23 also satisfy the above-mentioned composition formula (2).

[0146] In the solid electrolytes of Examples 22 to 23, the detailed mechanism of improved stability is not yet clear, but it is believed that: as cations, in addition to Na, each of the trivalent, tetravalent, and pentavalent elements contains at least one kind that contributes to stability. In addition, from the viewpoint of improved stability, it is preferred that the average ionic radius ratio is less than 0.526 as described above. The smaller average ionic radius ratio indicates that the bonding distance between the cation and Cl is shorter, and it is believed that the bonding force between the cation and Cl is higher. It is inferred that the height of the bonding force improves the stability as a material.

[0147] As described above, the present solid electrolyte comprises A, Mα, Mβ, Mγ and Cl. A is at least one element selected from the group consisting of Li and Na. Mα is at least one element selected from the group consisting of Zr and Hf. Mβ is at least one element selected from the group consisting of Ta and Nb. Mγ is at least one element selected from the group consisting of Gd, Yb, Dy, Er, Ho, Eu and Sc. The solid electrolyte has high ionic conductivity (initial conductivity), and maintains high ionic conductivity even in a dry room environment with a dew point of -40°C, and has high stability. Therefore, the solid electrolyte can be applied to the existing battery manufacturing process carried out in the dry room environment, and lithium ion batteries or sodium ion batteries can be easily manufactured. In order to achieve higher initial conductivity and stability, it is preferred that A contains Li, and it is more preferred that A is Li.

[0148] Preferably, the solid electrolyte is represented by the following composition formula:

[0149] A 6-(4+a-b)(1+c) (Mα (1-a-b) Mβ a Mγ b )1+c Cl 6

[0150] 0<a, 0<b, a+b<1, and -0.2≤c≤0.2 are satisfied. Thus, a solid electrolyte having high ion conductivity and high stability can be more reliably realized.

[0151] When A is Li, the value obtained by dividing the average ionic radius of Li, Mα, Mβ, and Mγ by the ionic radius of Cl (ie, the average ionic radius ratio) is preferably less than 0.424. This can more reliably improve the stability of the solid electrolyte.

[0152] When A is Na, the value obtained by dividing the average ionic radius of Na, Mα, Mβ, and Mγ by the ionic radius of Cl is preferably less than 0.526. This can more reliably improve the stability of the solid electrolyte.

[0153] The present solid electrolyte and all-solid secondary battery 1 can be modified in various ways.

[0154] The present solid electrolyte comprising Li, Mα, Mβ, Mγ and Cl may not satisfy the above composition formula (1). In addition, the average ion radius ratio may be greater than 0.424. Similarly, the present solid electrolyte comprising Na, Mα, Mβ, Mγ and Cl may not satisfy the above composition formula (2). In addition, the average ion radius ratio may be greater than 0.526.

[0155] The solid electrolyte can be mixed with other substances (including Li or Na) and used as an electrolyte material. In this case, the solid electrolyte is preferably the component with the largest mass ratio among the components contained in the electrolyte material, i.e., the main component. The mass ratio of the main component in the electrolyte material is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more.

[0156] The present solid electrolyte used in the all-solid secondary battery 1 does not necessarily need to be contained in all of the positive electrode 11, the negative electrode 12, and the electrolyte layer 13, but only needs to be contained in at least one of the positive electrode 11, the negative electrode 12, and the electrolyte layer 13. In addition, the present solid electrolyte can also be used in batteries other than all-solid secondary batteries, and can also be used for purposes other than batteries.

[0157] The configurations in the above-described embodiment and each modified example may be appropriately combined unless they are mutually contradictory.

[0158] Although the invention has been described and illustrated in detail, the above description is illustrative and not restrictive. Therefore, it can be seen that many modifications and variations can be adopted without departing from the scope of the present invention.

[0159] Explanation of symbols

[0160] 1 All-solid-state secondary battery

[0161] 11 Positive electrode

[0162] 12 Negative electrode

[0163] 13 Electrolyte layer

Claims

1. A solid electrolyte, wherein: Contains A, Mα, Mβ, Mγ and Cl, A is at least one element selected from the group consisting of Li and Na, Mα is at least one element selected from the group consisting of Zr and Hf, Mβ is at least one element selected from the group consisting of Ta and Nb, Mγ is at least one element selected from the group consisting of Gd, Yb, Dy, Er, Ho, Eu and Sc, The amount of Cl is greater than the amount of A.

2. The solid electrolyte according to claim 1, wherein A contains Li.

3. The solid electrolyte according to claim 1, wherein Mα contains Zr.

4. The solid electrolyte according to claim 1, wherein Mβ contains Ta.

5. The solid electrolyte according to claim 1, wherein Mγ contains Gd or Yb.

6. The solid electrolyte according to claim 1, wherein The solid electrolyte is represented by the following composition formula: A 6-(4+a-b)(1+c) (But (1-a-b) Mb a Mg b ) 1+c Cl6 It satisfies 0<a, 0<b, a+b<1 and -0.2≤c≤0.

2.

7. The solid electrolyte according to claim 1, wherein A is Li, The value obtained by dividing the average ionic radius of Li, Mα, Mβ, and Mγ by the ionic radius of Cl is less than 0.

424.

8. The solid electrolyte according to claim 1, wherein A is Na, The value obtained by dividing the average ionic radius of Na, Mα, Mβ, and Mγ by the ionic radius of Cl is less than 0.

526.

9. The solid electrolyte according to claim 1, wherein Contains no garnet structure. 10 . A battery comprising the solid electrolyte according to claim 1 .

Citation Information

Patent Citations

  • Halide solid electrolyte material and battery using this

    WO2020070956A1